The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.neuroscience.2011.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Differential ascending projections of temporomandibular joint-responsive brainstem neurons to periaqueductal gray and posterior thalamus of male and female rats

Abstract: Several craniofacial pain conditions including temporomandibular joint disorders (TMJD) are more prevalent in women than men. The basis for sex differences in deep craniofacial pain is not known. The present study compared the magnitude of ascending projections from TMJ-responsive neurons in trigeminal brainstem to the ventrolateral periaqueductal gray (vlPAG) or posterior nucleus of the thalamus (Po) in males and female rats. Fluorogold (FG) was injected into vlPAG or Po and TMJ-responsive neurons were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Tran et al (2017) also concluded that ARO/GABA cells in Vc were interneurons; however, they did not report sex differences. A similar number of Fos-positive neurons in Vc were produced in OvX and male rats after intra-TMJ injection of AIC consistent with previous studies in which Fos production was similar for male and diestrous females (Bereiter, 2001) and for males and OvX rats given low maintenance doses of E2 (Chang et al, 2012). There are several possible explanations for observing increased TMJ-evoked secretion of E2 in OvX females, but not in males.…”
Section: Discussionsupporting
confidence: 90%
“…Tran et al (2017) also concluded that ARO/GABA cells in Vc were interneurons; however, they did not report sex differences. A similar number of Fos-positive neurons in Vc were produced in OvX and male rats after intra-TMJ injection of AIC consistent with previous studies in which Fos production was similar for male and diestrous females (Bereiter, 2001) and for males and OvX rats given low maintenance doses of E2 (Chang et al, 2012). There are several possible explanations for observing increased TMJ-evoked secretion of E2 in OvX females, but not in males.…”
Section: Discussionsupporting
confidence: 90%
“…Fluorogold infusions into the ventrolateral portion of the PAG bilaterally labels neurons in the A2 region. 43 Thus, PAG activation may antidromically activate the A2 group to elicit vBNST release, or this release could arise from another unidentified mechanism. Second, selective chemical inactivation with DSP-4 and 6-OHDA strongly suggest that noradrenergic neurons of the LC are not responsible for release in the vBNST.…”
Section: Resultsmentioning
confidence: 99%
“…The symptoms of FMS in patients with mTMD are more severe and more prone to mental stress [ 22 , 23 ]. Both of TMD and FMS have higher incidence in female [ 20 , 24 ]. Because of this point, we used female rats to establish pre-clinical model to mimic the comorbidity of TMD and FMS.…”
Section: Discussionmentioning
confidence: 99%